Modified Diet Use in adults with Temporomandibular Disorders related to Rheumatoid Arthritis: A Systematic Review. - Gilheaney, Orla; Walshe, Margaret (My University, 2020)
Objective: Individuals presenting with rheumatoid arthritis (RA) frequently experience temporomandibular disorders (TMDs) which can result in limited ranges of mandibular motion, pain and fatigue on jaw function, and impaired mastication. As such, individuals with RA-related TMDs may consume a texture-modified diet in order to reduce the exacerbation of jaw pain and dysfunction and to increase the ease of oral intake. These softer food options may not contain the recommended nutrients, vitamins, and minerals, and therefore may not be nutritionally optimal. As unintentional body composition and weight changes are common in individuals with RA, there may be elevated risks of obesity or malnutrition in this patient subgroup. However, minimal research has been conducted to investigate the use of modified diets in this cohort and therefore, the true level of risk to these patients cannot not be adequately determined. The aim of this study was to determine the prevalence of diet modifications in adults presenting with RA affecting the TMJ. Methods: All available evidence presenting data on adults with RA who consume modified diets was systematically reviewed. A range of electronic databases were searched, including: EMBASE, PubMed, CINAHL, Web of Science, Elsevier Scopus, Science Direct, AMED, The Cochrane Database of Systematic Reviews, and ProQuest Dissertations and Theses A & I. Supplementary Google Scholar, reference list, and grey literature searches were also conducted. Independent reviewers assessed study eligibility, and methodological quality was rated using the Down’s and Black assessment. Results: One study was eligible for inclusion and half (50.82%; CI: 37.7-63.86) of individuals with RA in this study consumed a modified diet. This study was rated to be of moderate quality. The primary limitation of this review was the lack of studies on this topic which were available for inclusion. Conclusions: Although from clinical practice, it is recognised that adults with TMD related to RA do modify their diets to cope with the functional impairment of TMD, this review confirms that minimal research has been conducted regarding the use of texture modified diets by this population. This is despite concerns regarding unintentional weight changes in this patient group. Further research investigating this area is warranted in order to improve patient outcomes and experience of care.
PUBLISHED
Keywords: Rheumatoid arthritis; Diet; Diet modifications; Temporomandibular joint; Temporomandibular joint disorders; Ageing; Immunology, Inflammation & Infection; Inclusive Society; CHRONIC; DIET; DYSPHAGIA; RHEUMATOID ARTHRITIS; Age-related disability; Chronic Health Condition; Mobility impairment; Physical disability; Other